Correlation between Myocardial Strain and Angiographic Severity of Coronary Artery Disease in Non-ST-Elevation Myocardial Infarction Patient - Al-Amin, Md.; Alam, Md. Mashiul; Parvin, Tanjima; Ahmed, Chaudhury Meshkat; Abedin, Md. Zainal; Hossain, Mohammad Ashraf; Samsuzzaman, Sheikh Mohammad; Rashed, Md Rakibul Hasan; Dhar, Sukanta (International Journal of Innovative Research in Medical Science, 2020)
Background and objectives: Noninvasive assessment of coronary artery disease severity remains a clinical challenge. Myocardium subtended by obstructive coronary artery disease may show reduced left ventricular strain. The present study was intended to investigate whether this reduction of strain value correlates with increasing severity of coronary artery disease in Non-ST-Elevation Myocardial Infarction (NSTEMI) patients. Methods: This cross sectional study included 86 patients of NSTEMI. We assessed myocardial strain in global longitudinal strain (GLS) value using two dimensional speckle tracking echocardiography (2DSE). We performed coronary angiogram of the same patients and documented presence or absence of significant disease, number of affected vessels and Gensini score. Significant coronary artery was defined as ≥70% stenosis in any major coronary artery and or ≥50% stenosis in left main coronary artery. Results: Global longitudinal strain value was significantly lower in the significant coronary artery disease group (-13.5±3.4% vs. -19.01±2.3%) (p < 0.001). GLS declined proportionately with increasing severity of coronary artery disease defined by number of affected vessels (p < 0.001). Spearman’s rank correlation coefficient test between GLS value and Gensini score showed that the two variables maintained a linear but inverse relationship (ρ = 0.816, p < 0.001) that implies decreasing GLS is associated with increasing Gensini score. Multivariate logistic regression analysis found global longitudinal strain as an independent predictor of coronary artery disease. Conclusion: Myocardial strain assessed in global longitudinal strain value correlates with angiographic severity of coronary artery disease in patients with Non-ST-Elevation Myocardial Infarction.